Pengaruh Consumer Ethnocentrism, Harga dan Kualitas Produk Terhadap Citra Merek Brand Wildtime & Co - Janiarti; Handry Sudiartha Athar (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to analyze the influence of Consumer Ethnocentrism, Price, and Product Quality on Brand Image of Wildtime & Co. The data collection method uses a questionnaire. The population is 100 respondents, with a sample of 100. The analysis method uses multiple linear regression analysis using the Statistical Package For The Social Sciences (SPSS) tool. The results of the study show that first, Consumer Ethnocentrism has a positive and significant effect on Brand Image. Second, Price has a positive and significant effect on Brand Image. Third, Product Quality has a positive and significant effect on Brand Image. The results of the study can be used as a basis for increasing Consumer Ethnocentrism, Price, and Product Quality activities.